Patient, companion, and oncologist agreement regarding information discussed during triadic oncology clinical interactions. Issue 3 (15th February 2012) - Eggly, Susan; Penner, Louis A.; Hagiwara, Nao; Gonzalez, Richard; Harper, Felicity W. K.; Heath, Elisabeth I.; Albrecht, Terrance L.
Abstract Background Although people with cancer want and need information from their oncologists, patients and oncologists often disagree about what information was discussed during clinical interactions. Most patients have companions present during oncology visits; we investigated whether companions process information more accurately than patients. Specifically, we examined whether patients and companions differed in agreement with oncologists about what was discussed. We also investigated the effect of topic on agreement and patient/companion self‐reported understanding of discussions. Methods Patients with companions were invited to participate on first visits to a cancer center in Detroit, MI. Patients, companions, and oncologists independently completed questionnaires immediately following visits. Participants were asked whether five topics were discussed (diagnosis, prognosis, metastasis, treatment/treatment goals, and side effects) and, if discussed, what oncologists said. Participants were also asked to estimate their own and each other's understanding of discussions. Results A total of 66 patient–companion–oncologist triads participated. Agreement was higher regarding whether topics were discussed than what oncologists said. Agreement did not differ by dyad type. Patients, companions, and oncologists were equally likely to be the source of triadic disagreements. Agreement was high about diagnosis (>90%) but much lower about other topics, particularly side effects. Patients and companions reported greater understanding of discussions than oncologists estimated and more accurately estimated each other's understanding than did oncologists. Conclusions Companions and patients showed similar levels of agreement with oncologists about what they discussed during visits. Interventions are needed to improve communication of information to both patients and companions, especially about particular topics. Copyright © 2012 John Wiley & Sons, Ltd.